MENINGKATKAN EKONOMI MASYARAKAT MELALUI HASIL PERTANIAN TEMBAKAU KELURAHAN KARANG DALEM KABUPATEN SAMPANG - Nuruddin Nuruddin (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2021)
AbstractTobacco is a favorite of farmers in the Karang Dalem district. The cultivation and purchasing of tobacco also affect labor, productivity, and industry. Productivity is needed to increase the work of tobacco farmers. The study uses qualitative descriptive using ethnographic methods. Ethnographic methods are a method used to identify and describe a community situation in order to understand the goals and views of the local people. This method of research should jump in and interact with people which is an object of study. Data collection techniques in this study by conducting interviews, participative observations, and documenting. The data used in the study are the primary and secondary data. Primary data comes from interviews, observations, respondent's log, and documentation. Whereas secondary data are obtained from journals and the Internet. In the results of this study, it explained that the role of labor is needed to increase productivity in tobacco farming. The tobacco barons and workers play an important role in the increase in the production of tobacco farming. In addition, wages and compensation were needed to support the subsistence of the tobacco farmer.Key words: labor, productivity, tobacco growers